(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article deals with the peculiarities of functioning of non-elementary compound sentences with cause-subordinate clause in the prose literary works of modern Ukrainian writers; their structural-semantic and notional types are distinguished.